2018
DOI: 10.1101/266171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphorylation of the exocyst subunit Exo70B2 contributes to the regulation of its function

Abstract: The exocyst is a conserved hetero-octameric complex that mediates early tethering of post-Golgi vesicles during exocytosis. Its Exo70 subunit functions as a spatiotemporal regulator by mediating numerous interactions with proteins and lipids. However, a molecular understanding of the exocyst functions remains challenging. Exo70B2 localized to dynamic foci at the plasma membrane and transited through Brefeldin A (BFA)-sensitive compartments, indicating that it participates in conventional secretion. Conversely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…binding (Teh et al, 2019) and AtExo70E2-AtNBR1-AtATG8 interaction (this study), respectively. It would be interesting to determine how other exocyst components are recruited to autophagosomes as well as their physiological significance in plants in future studies.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…binding (Teh et al, 2019) and AtExo70E2-AtNBR1-AtATG8 interaction (this study), respectively. It would be interesting to determine how other exocyst components are recruited to autophagosomes as well as their physiological significance in plants in future studies.…”
Section: Discussionsupporting
confidence: 52%
“…However, it remains largely elusive as to whether and how the exocyst subunits would be turned over via the autophagic pathways in yeast, animal cells, and plants. A recent study showed that autophagy induction by flg22 or BTH treatment results in vacuolar delivery of AtExo70B2 for degradation via direct AtExo70B2-AtATG8 (AIM motif) interaction (Teh et al, 2019), indicating that autophagy may regulate exocyst homeostasis in plants. Indeed, in addition to AtExo70E2, CNX-mCherry-AtNBR1 can also recruit other exocyst subunits including AtSec5 and AtExo84 (Supplemental Figure 7), indicating the possible role of AtNBR1-mediated selective autophagy for regulating exocyst homeostasis in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of direct evidence for ATG8 binding, Exo70B1 is colocalized with the ATG8f in Arabidopsis (Kulich et al, 2013). Further, Exo70B2 has been demonstrated to interact with ATG8, an interaction enhanced by phosphorylation of MPK3 kinase that leads to autophagic recycling of Exo70B2 (Teh et al, 2018). These results suggest that Exo70B1 and Exo70B2 may be involved in autophagic transport into the vacuole.…”
Section: Non-autophagic Roles Of Atg8 Proteins In Plantsmentioning
confidence: 91%
“…EXO70s are subunits of the octomeric exocyst complex, which is involved in exocytosis and other cellular trafficking processes. Recent studies have shown that EXO70 paralogs could also play roles in autophagy 17, 50, 51 . EXO70D3 interacted with ARR5 D87E , but not with a wild-type ARR5 or ARR5 D87A bait in a yeast two-hybrid assay (Fig.…”
Section: Resultsmentioning
confidence: 99%